Perceptions regarding the multidisciplinary treatment of patients with severe trauma in Korea: a survey of trauma specialists - Shin Ae Lee; Yeon Jin Joo; Ye Rim Chang (Journal of Trauma and Injury)
Purpose Patients with multiple trauma necessitate assistance from a wide range of departments and professions for their successful reintegration into society. Historically, the primary focus of trauma treatment in Korea has been on reducing mortality rates. This study was conducted with the objective of evaluating the current state of multidisciplinary treatment for patients with severe trauma in Korea. Based on the insights of trauma specialists (i.e., medical professionals), we aim to suggest potential improvements. Methods An online questionnaire was conducted among 871 surgical specialists who were members of the Korean Society of Traumatology. The questionnaire covered participant demographics, current multidisciplinary practices, perceived challenges in collaboration with rehabilitation, psychiatry, and anesthesiology departments, and the perceived necessity for multidisciplinary treatment. Results Out of the 41 hospitals with which participants were affiliated, only nine conducted multidisciplinary meetings or rounds with nonsurgical departments. The process of transferring patients to rehabilitation facilities was not widespread, and delays in these transfers were frequently observed. Financial constraints were identified by the respondents as a significant barrier to multidisciplinary collaboration. Despite these hurdles, the majority of respondents acknowledged the importance of multidisciplinary treatment, especially in relation to rehabilitation, psychiatry, and anesthesiology involvement. Conclusions This survey showed that medical staff specializing in trauma care perceive several issues stemming from the absence of a multidisciplinary system for patient-centered care in Korea. There is a need to develop an effective multidisciplinary treatment system to facilitate the recovery of trauma patients.